Knowledge co-creation in the 21st century: A cross-country experience-based policy report - Kreiling, Laura; Paunov, Caroline (OECD Science, Technology and Industry Policy Papers, 2021)
The importance of knowledge co-creation – the joint production of innovation between industry, research and possibly other stakeholders, such as civil society – has been increasingly acknowledged. This paper builds on 13 cross-country case studies and co-creation experiences during the COVID-19 pandemic to characterise the diversity of knowledge co-creation initiatives and identify lessons for policy. The paper identifies a strong rationale for policy to support knowledge co-creation because the benefits of successful co-creation initiatives outweigh the initial co-ordination costs. Moreover, knowledge co-creation initiatives can contribute to democratising innovation. Successful initiatives engage all stakeholders and have effective governance and management structures. They also have clearly defined ownership and use rights of the collaborations’ outcomes and benefit from favourable conditions to operate, including temporary staff mobility and institutional set-ups that facilitate collaboration and effective communication among participants.
Keywords: COVID-19; Co-création; Innovation collaborative; OCDE; Politiques; Réservé UdeM; Science industrielle

Knowledge co-creation in the 21st century: A cross-country experience-based policy report - Kreiling, Laura; Paunov, Caroline (OECD Science, Technology and Industry Policy Papers, 2021)
The importance of knowledge co-creation – the joint production of innovation between industry, research and possibly other stakeholders, such as civil society – has been increasingly acknowledged. This paper builds on 13 cross-country case studies and co-creation experiences during the COVID-19 pandemic to characterise the diversity of knowledge co-creation initiatives and identify lessons for policy. The paper identifies a strong rationale for policy to support knowledge co-creation because the benefits of successful co-creation initiatives outweigh the initial co-ordination costs. Moreover, knowledge co-creation initiatives can contribute to democratising innovation. Successful initiatives engage all stakeholders and have effective governance and management structures. They also have clearly defined ownership and use rights of the collaborations’ outcomes and benefit from favourable conditions to operate, including temporary staff mobility and institutional set-ups that facilitate collaboration and effective communication among participants.
Keywords: COVID-19; Co-création; Innovation collaborative; OCDE; Politiques; Réservé UdeM; Science industrielle